HARMONIES OF ANTIQUITY: EXPLORING THE VEDIC SYMPHONY OF MUSIC AND DANCE: A HISTORICAL PERSPECTIVE - Mishra, Sanjeev Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Music, a cherished aspect of the cultural fabric of ancient Bharatvarsha (India), flourished as one of the prominent Vedic arts. Believed to have originated from the Gandharva Veda, music was integral to the lives of the people for countless generations, signifying their advanced understanding of melody and rhythm. This art form, foundational to the Sama Veda for chanting mantras, boasts an unparalleled legacy, enriched with intricate Ragas and Ragnis that often elude the untrained ear.